(3LOhd GdjhGbjJ aj eYQaI GdehGbjJ hGdWGdY hGdZGQH hMdhd GdTeS aj GdHQhL heYQaI eYGde GdRQGYIs
(3ChdgG (B:s
(3TgQ GdChd Ghd PQi GdHQ s
(3BNQgG (B:s
(3Je Pdc HYhf Gddg s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3Hg Tcd JhVjMi jTHg GdGSWQdGHs
(3LGA ai GNQg LOhd ef JCdja GdTjN YHO GdQMef HGZhK Hf Ydi Hf CMeO Hf CHj HcQs
(3eSJNQL ef JGQjN CHj GdYbhd s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdadcs